Competitiveness, Marketing Access, and Network Capability and Its Impacts on Marketing Performance - Sayekti, Teguh Iman; Soliha, Euis (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2016)
This study is to determine what factors influencingthe performance of SMEs. The population in this study is SMEs in the Central Java. Sample collection was conducted with a purposive sampling method. Criteriaused to take into accountis the SMEs that are already running at leastfortwo years. The sample in this study is intended as the representative of total population,67 (sixty seven). The data were processed and analyzed by computer program of SPSS 20 for Windows. Based on the results of regression analysis, it can be concluded that competitiveness has positive and significant impact on marketing performance marketing access has positive and significant impact on marketing performance. It means that the higher competitiveness and marketing access, the higher its performance. Competitiveness and marketing access have influence on SMEs performance through network capability.